Augmented Reality based Gamified Mandarin Learning Application - Adam, Steffi; Marfuah, Marfuah; Afifah, Ummul Fitri; Abdullah, Abdullah (Sistemasi: Jurnal Sistem Informasi, 2024)
Most Chinese-heritage parents will teach their children Mandarin as early as possible. Parents will do various things such as providing additional Mandarin tutoring or enrolling their children in schools that teach Mandarin. Unfortunately, many children become bored and unwilling to learn Mandarin because Mandarin has a complex language structure, starting from writing, pronunciation, and grammar. This study aims to develop a Mandarin language learning application based on augmented reality that incorporates gamification elements to increase children's learning motivation. The development method used is waterfall. The results of this study show that with the existence of a gamified Mandarin language learning application based on augmented reality, Mandarin learning becomes more tangible, thus it is expected to facilitate increasing children's motivation to learn Mandarin.